Ammonia oxidation catalyst, nitrogen-oxygen sensor chip and preparation method of nitrogen-oxygen sensor chip
By coating the ammonia oxidation catalyst on the intake head of the nitrogen oxygen sensor, catalyzing the conversion of NH3 to N2 and H2O, the problem of inaccurate accuracy of NOx sensor in the presence of NH3 is solved, and the accurate identification of NOx concentration and the stability of the sensor is improved.
Patent Information
- Application Number
- CN202510151728.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the presence of NH3, the NOx output value is too high, the accuracy is inaccurate, and the electrochemical NH3 sensor is consumed and has insensitive response.
An ammonia oxidation catalyst is provided, coated on the intake head of the nitrogen oxygen sensor, and catalyzed the conversion of NH3 into N2 and H2O at high temperature to avoid cross-induction of NH3, thereby achieving accurate identification of NOx concentration in the exhaust gas.
The accurate identification of NOx concentration in the exhaust gas is achieved, the accuracy and stability of the sensor are improved, the catalyst has high N2 selectivity, and can still maintain high activity after long-term use.
Smart Images

Figure CN119633828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nitrogen oxygen sensors, and in particular to an ammonia oxidation catalyst, a nitrogen oxygen sensor chip and a preparation method thereof. Background Art
[0002] At present, the purification treatment of domestic chemical waste gas and heavy-duty commercial diesel vehicle exhaust almost all adopts SCR (selective catalytic reduction) scheme to control NOx. The SCR method can selectively react NH3 with NOx in the exhaust gas to produce N2 and H2O that are pollution-free to the environment. However, when the SCR system is closed-loop controlled, it is difficult to accurately control the injection amount of urea aqueous solution, and the SCR catalytic converter will inevitably have NH3 escape. When the SCR system uses an electrochemical nitrogen oxide sensor, there is an NH3 cross-sensing defect. Once NH3 escape occurs, the detection value of the downstream nitrogen oxide sensor will be higher than the actual value, resulting in overspray of the system urea solution, which leads to a vicious cycle. This gas with a strong irritating odor and corrosiveness will cause serious harm to the natural environment and human health.
[0003] The nitrogen oxide sensor is an electronic component based on oxygen ion conduction of functional ceramics. It uses multi-layer high-temperature co-fired ceramic technology to sinter a porous metal ceramic composed of precious metals such as Pt, Au, Rh and ZrO2 on a YSZ (yttrium stabilized zirconia) substrate to analyze and collect micro-electric signals, thereby identifying NOx characteristic signals. However, when the NOx sensor is working, the temperature of the chamber is higher than 800°C. The escaped NH3 enters the high-temperature chamber and can be mostly converted into NOx under the catalytic action of the precious metal electrodes. This part of NOx will be detected by the sensor, making the detection value higher, resulting in a large deviation in the sensor detection.
[0004] One way to solve the NH3 cross-induction problem in nitrogen oxide sensors is to set an adsorption device outside the sensor to adsorb and remove the NH3 carried in the exhaust gas, so that the nitrogen oxide sensor cannot contact NH3; but the adsorption capacity of the adsorption device is limited. After reaching the adsorption capacity limit, the adsorption device will also fail. Another method is to propose a computer-trained deep neural network model to automatically decode NOx and NH3 in the exhaust gas, thereby eliminating NH3 cross-induction. In addition, most of the electrochemical NH3 sensors on the market are consumable. When exposed to an environment with NH3, the consumable NH3 sensors continuously consume the sensitive substances in the sensor. As the NH3 sensitive substances are consumed, the sensor's response will also become insensitive.
[0005] In view of this, this application is hereby filed. Summary of the invention
[0006] The problem with the prior art is that the existing NOx sensor in the presence of NH3 leads to a high NOx output value and inaccurate accuracy. In order to solve the above problem, the present invention provides an ammonia oxidation catalyst, a nitrogen oxide sensor chip and a preparation method thereof, discloses an NH3 oxidation catalyst with high N2 selectivity at high temperature, which is coated on the intake head of the nitrogen oxide sensor, so that NH3 can be converted into N2 and H2O that have no effect on NOx detection before entering the sensor chamber, thereby realizing accurate identification of NOx concentration in exhaust gas.
[0007] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides an ammonia oxidation catalyst, comprising the following components by mass fraction: 100 parts of catalyst powder, 1 to 20 parts of pore former, 10 to 20 parts of binder, 0.5 to 5 parts of thickener, 0.5 to 5 parts of defoamer and 10 to 20 parts of solvent; The catalyst powder includes a catalyst carrier and a catalytically active component supported on the catalyst carrier; The precursor salt used for the catalytically active component is one or more of ferric nitrate, nickel nitrate, ferric chloride, nickel chloride, and copper nitrate; The catalyst carrier is one or more of SiC, SiO2, γ-Al2O3, and ZrO2.
[0008] In a specific embodiment, the pore-forming agent is one or more of carbon powder, polymethyl methacrylate, starch, and polyvinyl pyrrolidone.
[0009] In a specific embodiment, the binder is one or more of alumina sol, silica sol, and diaspore; the thickener is one or more of gelatin, carboxymethyl cellulose, dextrin, and gum arabic.
[0010] In a specific embodiment, the defoaming agent is one or more of polydimethylsiloxane, polyoxypropylene glyceryl ether, and stearic acid glycol ester; the solvent is one or a mixture of deionized water, ethanol, glycerol, and acetic acid.
[0011] In a second aspect, the present invention provides a method for preparing an ammonia oxidation catalyst, comprising the following steps: 1) Weigh the precursor salt according to the mass ratio of the catalytically active components required after calcination, and add it into water to dissolve; 2) Add the catalyst carrier, transfer to an oil bath, stir and heat until the water in the beaker is completely evaporated; 3) Collect the solid matter and grind it, and finally calcine the powdered catalyst in a muffle furnace to obtain catalyst powder; 4) The catalyst powder is mixed with a pore former, a binder, a thickener, a defoamer and a solvent, and mixed in a ball mill to obtain an ammonia oxidation catalyst slurry.
[0012] In a specific embodiment, in step 2), an oil bath is used for stirring and heating at a temperature of 50-200° C.; In the step 3), the calcination temperature is 500-900° C. and the temperature is kept for 2-6 hours.
[0013] In a third aspect, the present invention provides a nitrogen oxide sensor chip, wherein the outside of the air inlet of the nitrogen oxide sensor chip is coated with the ammonia oxidation catalyst or the ammonia oxidation catalyst obtained by the preparation method.
[0014] In a specific embodiment, the coating thickness of the ammonia oxidation catalyst is 100-800 μm, more preferably 200-600 μm.
[0015] In a fourth aspect, the present invention provides a method for preparing a nitrogen oxygen sensor chip, comprising the following steps: 1) Use a sealing agent to seal the air inlet head of the sensor chip; 2) vertically placing the sensor chip into the catalyst slurry, so that the head of the sensor chip is immersed in the catalyst slurry and is completely covered by the slurry; 3) After dipping for a certain period of time, the sensor chip is pulled upward to complete one dipping, dried, and then the dipping and drying processes are repeated. Finally, the sensor chip is baked to obtain the nitrogen oxygen sensor chip.
[0016] In a specific embodiment, in step 3), the immersion time is 10-80s, the pulling speed is 50-1000 μm / s, the immersion and pulling are repeated 1-N times, N is an integer greater than 1, and the drying temperature is 45-150°C.
[0017] In a specific embodiment, the sealing agent is one or more of polyvinyl butyral, vaseline, and polyvinyl pyrrolidone.
[0018] The catalytic material coated at the air inlet of the nitrogen oxygen sensor in the present invention has a porous structure, and its working principle is: NH3 escaping from the exhaust gas diffuses into the coated porous catalyst before entering the reaction chamber. When the sensor is working, the temperature of the porous catalyst is greater than 800°C. At this temperature, NH3 reacts under the catalysis of the catalyst: 4NH3+ 3O2= 2N2+ 6H2O, converting NH3 into N2, and then enters the first chamber of the sensor chip through the diffusion channel. There is almost no NH3 in the gas, which can eliminate the cross-induction of NH3. In the first chamber, the O2 content in the gas is adjusted, and the pump voltage is applied to the main pump to pump O2 in or out, generating a limiting current IP0, and the oxygen is controlled at about a few ppm. The reducing gas is oxidized into gases such as CO2 and H2O that have no effect on NOx detection, and the main components of the exhaust gas will become NOx and extremely low concentration O2; after the gas in the first chamber diffuses into the second chamber, the low concentration of O2 will be further pumped out by the auxiliary pump, and at this time, NOx will be completely converted into NO due to the influence of chemical equilibrium; on the electrode of the measuring pump, NO will undergo a decomposition reaction: 2NO = N2 + O2, and the O2 produced by the decomposition will be pumped out, thereby forming a limiting pump current IP2. The size of the pump current is proportional to the concentration of NO. By collecting and calculating the micro-electric signal IP2, the NOx concentration in the exhaust gas can be accurately identified. The internal structure and related control parameters of the nitrogen oxide sensor mentioned in the present invention are all prior art, so they will not be elaborated here.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. An ammonia oxidation catalyst, a nitrogen oxide sensor chip and a preparation method thereof provided in an embodiment of the present invention are coated on the intake head of the nitrogen oxide sensor, so that NH3 can be converted into N2 and H2O which have no effect on NOx detection before entering the sensor chamber, thereby realizing accurate identification of NOx concentration in exhaust gas; 2. An ammonia oxidation catalyst, a nitrogen oxide sensor chip and a preparation method thereof provided in an embodiment of the present invention have a simple preparation process, and the raw materials are cheap and readily available. The active components of the catalyst can be evenly distributed and have a strong bonding force with the sensor chip, and are not easy to fall off or crack. 3. An ammonia oxidation catalyst, a nitrogen oxide sensor chip and a preparation method thereof provided by an embodiment of the present invention, the reaction temperature required for the catalytic material for catalyzing the conversion of NH3 into N2 is provided by the temperature of the sensor when it is working normally, and the temperature is constant. The catalyst has high N2 selectivity and can still maintain high activity after long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 It is a schematic diagram of the related control of the existing nitrogen oxygen sensor; Figure 2 Schematic diagram of the structure of a nitrogen oxygen sensor coated with a porous catalyst; Figure 3 This is a SEM image of the porous catalyst coating at the inlet of the nitrogen oxygen sensor head provided in Example 1 of the present invention; Figure 4 This is a SEM image of the 30%Fe-10%Ni / γ-Al2O3 catalyst provided in Example 1 of the present invention; Figure 5 The XRD pattern of the 30%Fe-10%Ni / γ-Al2O3 catalyst provided in Example 1 of the present invention; Figure 6 This is a test diagram of the electrical performance of the nitrogen oxygen sensor provided in Example 1 of the present invention at different NH3 concentrations; Figure 7 This is a stability test diagram of the nitrogen oxygen sensor provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0023] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known materials or methods are not specifically described.
[0024] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0025] In the description of the present invention, the directions or positional relationships indicated by terms such as “front”, “rear”, “left”, “right”, “up”, “down”, “vertical”, “horizontal”, “high”, “low”, “inside” and “outside” are based on the directions or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limiting the scope of protection of the present invention.
[0026] At present, one of the methods to solve the NH3 cross-induction of nitrogen oxide sensors is to set an adsorption device outside the sensor to adsorb and remove the NH3 entrained in the exhaust gas, so that the nitrogen oxide sensor cannot contact NH3; but the adsorption capacity of the adsorption device is limited. After reaching the adsorption capacity limit, the adsorption device will also fail. Another method is to propose a computer-trained deep neural network model to automatically decode NOx and NH3 in the exhaust gas, thereby eliminating NH3 cross-induction. In addition, most of the electrochemical NH3 sensors on the market are consumable. When exposed to an environment with NH3, the consumable NH3 sensors continuously consume the sensitive substances in the sensor. As the NH3 sensitive substances are consumed, the response of the sensor will also become insensitive.
[0027] In order to solve the above technical problems: In a first aspect, the present invention provides an ammonia oxidation catalyst, comprising the following components by mass fraction: 100 parts of catalyst powder, 1 to 20 parts of pore former, 10 to 20 parts of binder, 0.5 to 5 parts of thickener, 0.5 to 5 parts of defoamer and 10 to 20 parts of solvent; The catalyst powder includes a catalyst carrier and a catalytically active component supported on the catalyst carrier; The precursor salt used for the catalytically active component is one or more of ferric nitrate, nickel nitrate, ferric chloride, nickel chloride, and copper nitrate; The catalyst carrier is one or more of SiC, SiO2, γ-Al2O3, and ZrO2.
[0028] In a specific embodiment, the pore-forming agent is one or more of carbon powder, polymethyl methacrylate, starch, and polyvinyl pyrrolidone.
[0029] In a specific embodiment, the binder is one or more of alumina sol, silica sol, and diaspore; the thickener is one or more of gelatin, carboxymethyl cellulose, dextrin, and gum arabic.
[0030] In a specific embodiment, the defoaming agent is one or more of polydimethylsiloxane, polyoxypropylene glyceryl ether, and stearic acid glycol ester; the solvent is one or a mixture of deionized water, ethanol, glycerol, and acetic acid.
[0031] In a second aspect, the present invention provides a method for preparing an ammonia oxidation catalyst, comprising the following steps: 1) Weigh the precursor salt according to the mass ratio of the catalytically active components required after calcination, and add it into water to dissolve; 2) Add the catalyst carrier, transfer to an oil bath, stir and heat until the water in the beaker is completely evaporated; 3) Collect the solid matter and grind it, and finally calcine the powdered catalyst in a muffle furnace to obtain catalyst powder; 4) The catalyst powder is mixed with a pore former, a binder, a thickener, a defoamer and a solvent, and mixed in a ball mill to obtain an ammonia oxidation catalyst slurry.
[0032] In a specific embodiment, in step 2), an oil bath is used for stirring and heating at a temperature of 50-200° C.; In the step 3), the calcination temperature is 500-900° C. and the temperature is kept for 2-6 hours.
[0033] In a third aspect, the present invention provides a nitrogen oxide sensor chip, wherein the outside of the air inlet of the nitrogen oxide sensor chip is coated with the ammonia oxidation catalyst or the ammonia oxidation catalyst obtained by the preparation method.
[0034] In a specific embodiment, the coating thickness of the ammonia oxidation catalyst is 100-800 μm, more preferably 200-600 μm.
[0035] In a fourth aspect, the present invention provides a method for preparing a nitrogen oxygen sensor chip, comprising the following steps: 1) Use a sealing agent to seal the air inlet head of the sensor chip; 2) vertically placing the sensor chip into the catalyst slurry according to claim 5, so that the head of the sensor chip is immersed in the catalyst slurry and is completely covered by the slurry; 3) After dipping for a certain period of time, the sensor chip is pulled upward to complete one dipping, dried, and then the dipping and drying processes are repeated. Finally, the sensor chip is baked to obtain the nitrogen oxygen sensor chip.
[0036] In a specific embodiment, in step 3), the immersion time is 10-80s, the pulling speed is 50-1000 μm / s, the immersion and pulling are repeated 1-N times, N is an integer greater than 1, and the drying temperature is 45-150°C.
[0037] In a specific embodiment, the sealing agent is one or more of polyvinyl butyral, vaseline, and polyvinyl pyrrolidone.
[0038] like Figure 1 and Figure 2 As shown, the catalytic material coated at the air inlet of the nitrogen oxygen sensor in the present invention has a porous structure, and its working principle is: NH3 escaping in the exhaust gas diffuses into the coated porous catalyst before entering the reaction chamber. When the sensor is working, the temperature of the porous catalyst is greater than 800°C. At this temperature, NH3 reacts under the catalysis of the catalyst: 4NH3+3O2= 2N2+ 6H2O, converting NH3 into N2, and then enters the first chamber of the sensor chip through the diffusion channel. There is almost no NH3 in the gas, which can eliminate the cross-induction of NH3. In the first chamber, the O2 content in the gas is adjusted, and O2 is pumped in or out by applying a pump voltage to the main pump, generating a limiting current IP0, and the oxygen is controlled at around a few ppm. The reducing gas is oxidized into gases such as CO2 and H2O that have no effect on NOx detection, and the main components of the exhaust gas will become NOx and extremely low concentration O2; after the gas in the first chamber diffuses into the second chamber, the low concentration of O2 will be further pumped out by the auxiliary pump, and at this time, NOx will be completely converted into NO due to chemical equilibrium; on the electrode of the measuring pump, NO will undergo a decomposition reaction: 2NO = N2 + O2, and the O2 produced by the decomposition will be pumped out, thereby forming a limiting pump current IP2. The size of the pump current is proportional to the concentration of NO. By collecting and calculating the micro-electric signal IP2, the NOx concentration in the exhaust gas can be accurately identified.
[0039] Example 1 An embodiment of the present invention provides a method for preparing a nitrogen oxygen sensor, comprising the following steps: (1) Catalyst powder preparation Weigh 16.907g of ferric chloride hexahydrate and 5.3049g of nickel chloride hexahydrate, add them to a beaker filled with 30mL of deionized water, and place them in an ultrasonic oscillator for ultrasonic dissolution. After the precursor salt is fully dissolved, add 10g of γ-Al2O3 carrier with an average particle size of 50nm. After ultrasonication for 30min, transfer to an oil bath for stirring and heating. The heating temperature is set to 90℃. After the solution becomes molten, set the heating temperature to 150℃ until the water in the beaker is completely evaporated. Collect the solid material and grind it thoroughly. Put the ground powder in a crucible, heat it to 800℃ in a muffle furnace at a heating rate of 5℃ / min, keep it warm for 4h, and obtain 30%Fe-10%Ni / γ-Al2O3 catalyst powder after annealing. The surface and composition of the obtained 30%Fe-10%Ni / γ-Al2O3 catalyst powder are characterized. The results are as follows: Figure 4 and Figure 5 shown.
[0040] (2) Preparation of coating catalyst slurry Weigh 10 g of the catalyst powder obtained in step (1) into a ball mill, and then add 1.5 g of polymethyl methacrylate, 2 g of aluminum sol, 0.2 g of carboxymethyl cellulose, 0.2 g of polyoxypropylene glycerol ether, and 1 g of glycerol in sequence, and finally add zirconium balls with average diameters of 5 mm and 8 mm, with a total mass of 25 g of zirconium balls; ball mill for 15 min in a planetary ball mill at a speed of 800 r / min, filter out the zirconium balls after ball milling, and obtain a 30% Fe-10% Ni / γ-Al2O3 catalyst slurry.
[0041] (3) Catalyst slurry coating After chamfering the air inlet head of the sensor chip, use polyvinyl butyral to seal the air inlet head, use an immersion and pulling machine to completely immerse the chip head in the catalyst slurry, immerse for 30 seconds, pull it up at a speed of 100μm / s, put it in a 50℃ oven to dry after coating, repeat the immersion and drying, and then place it in a muffle furnace and bake it at 900℃ for 2h. After annealing, a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and its coating thickness is measured to be 516μm. Figure 3 This is a SEM image of the porous catalyst coating at the inlet of the nitrogen oxygen sensor head prepared in this embodiment.
[0042] Example 2 An embodiment of the present invention provides a method for preparing a nitrogen oxygen sensor, comprising the following steps: (1) Catalyst powder preparation Weigh 33.734 of ferric nitrate nonahydrate, add it to a beaker filled with 40 mL of deionized water, and place it in an ultrasonic oscillator for ultrasonic dissolution. After the precursor salt is fully dissolved, add 10 g of γ-Al2O3 carrier with an average particle size of 50 nm. After ultrasonication for 30 minutes, transfer it to an oil bath for stirring and heating. The heating temperature is set to 90°C. After the solution becomes a molten state, set the heating temperature to 150°C until the water in the beaker is completely evaporated. Collect the solid material and grind it thoroughly. The ground powder is placed in a crucible and heated to 800°C in a muffle furnace at a heating rate of 5°C / min. Keep warm for 4 hours and anneal to obtain 40% Fe / γ-Al2O3 catalyst powder.
[0043] (2) Preparation of coating catalyst slurry Weigh 10 g of the catalyst powder obtained in step (1) into a ball mill, and then add 1.5 g of polymethyl methacrylate, 2 g of aluminum sol, 0.2 g of carboxymethyl cellulose, 0.2 g of polyoxypropylene glycerol ether, and 1 g of glycerol in sequence, and finally add zirconium balls with average diameters of 5 mm and 8 mm, with a total mass of 25 g of zirconium balls; ball mill for 15 min in a planetary ball mill at a speed of 800 r / min, filter out the zirconium balls after ball milling, and obtain a 40% Fe / γ-Al2O3 catalyst slurry.
[0044] (3) Catalyst slurry coating After chamfering the air inlet head of the sensor chip, use polyvinyl butyral to seal the air inlet head, use an immersion and pulling machine to completely immerse the chip head in the catalyst slurry, immerse for 30 seconds, pull it upward at a speed of 100μm / s, and dry it in a 50℃ oven after coating. Repeat the immersion and drying, then place it in a muffle furnace and bake it at 900℃ for 2h. After annealing, a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and its coating thickness is measured to be 448μm.
[0045] Example 3 An embodiment of the present invention provides a method for preparing a nitrogen oxygen sensor, comprising the following steps: (1) Catalyst powder preparation Weigh 5.64g of ferric chloride hexahydrate and 15.912g of nickel chloride hexahydrate, add them to a beaker filled with 30mL of deionized water, and place them in an ultrasonic oscillator for ultrasonic dissolution. After the precursor salt is fully dissolved, add 10g of SiO2 carrier with an average particle size of 50nm. After ultrasonication for 30min, transfer to an oil bath for stirring and heating. The heating temperature is set to 90℃. After the solution becomes a molten state, set the heating temperature to 150℃ until the water in the beaker is completely evaporated. Collect the solid material and grind it thoroughly. Put the ground powder into a crucible and heat it to 800℃ in a muffle furnace at a heating rate of 5℃ / min. Keep it warm for 4h and anneal to obtain 10%Fe-30%Ni / SiO2 catalyst powder.
[0046] (2) Preparation of coating catalyst slurry Weigh 10 g of the catalyst powder obtained in step (1) into a ball mill, and then add 1.5 g of polymethyl methacrylate, 2 g of aluminum sol, 0.2 g of carboxymethyl cellulose, 0.2 g of polyoxypropylene glycerol ether, and 1 g of glycerol in sequence, and finally add zirconium balls with average diameters of 5 mm and 8 mm, with a total mass of 25 g of zirconium balls; ball mill for 15 min in a planetary ball mill at a speed of 800 r / min, filter out the zirconium balls after ball milling, and obtain a 10% Fe-30% Ni / SiO2 catalyst slurry.
[0047] (3) Catalyst slurry coating After chamfering the air inlet head of the sensor chip, use polyvinyl butyral to seal the air inlet head, use an immersion and pulling machine to completely immerse the chip head in the catalyst slurry, immerse for 30 seconds, pull it upward at a speed of 100μm / s, and dry it in a 50℃ oven after coating. Repeat the immersion and drying, then place it in a muffle furnace and bake it at 900℃ for 2h. After annealing, a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and its coating thickness is measured to be 428μm.
[0048] Example 4 An embodiment of the present invention provides a method for preparing a nitrogen oxygen sensor, comprising the following steps: (1) Catalyst powder preparation Weigh 21.217g of nickel chloride hexahydrate, add it to a beaker filled with 30mL of deionized water, and place it in an ultrasonic oscillator for ultrasonic dissolution. After the precursor salt is fully dissolved, add 10g of γ-Al2O3 carrier with an average particle size of 50nm. After ultrasonication for 30min, transfer it to an oil bath for stirring and heating. The heating temperature is set to 90℃. After the solution becomes a molten state, set the heating temperature to 150℃ until the water in the beaker is completely evaporated. Collect the solid material and grind it thoroughly. The ground powder is placed in a crucible and heated to 800℃ in a muffle furnace at a heating rate of 5℃ / min. Keep warm for 4h and anneal to obtain 40% Ni / γ-Al2O3 catalyst powder.
[0049] (2) Preparation of coating catalyst slurry Weigh 10 g of the catalyst powder obtained in step (1) into a ball mill, then add 1 g of carbon powder, 2 g of aluminum sol, 0.2 g of carboxymethyl cellulose, 0.2 g of polyoxypropylene glycerol ether, and 1 g of glycerol in sequence, and finally add zirconium balls with average diameters of 5 mm and 8 mm, with a total mass of 25 g of zirconium balls; ball mill for 15 min in a planetary ball mill at a speed of 800 r / min, filter out the zirconium balls after ball milling, and obtain a 40% Ni / γ-Al2O3 catalyst slurry.
[0050] (3) Catalyst slurry coating After chamfering the air inlet head of the sensor chip, use polyvinyl butyral to seal the air inlet head, use an immersion and pulling machine to completely immerse the chip head in the catalyst slurry, immerse for 30 seconds, pull it upward at a speed of 100μm / s, and dry it in a 50℃ oven after coating. Repeat the immersion and drying, then place it in a muffle furnace and bake it at 900℃ for 2h. After annealing, a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and its coating thickness is measured to be 459μm.
[0051] Example 5 An embodiment of the present invention provides a method for preparing a nitrogen oxygen sensor, comprising the following steps: (1) Catalyst powder preparation Weigh 11.284g of ferric chloride hexahydrate and 10.608g of nickel chloride hexahydrate, add them to a beaker filled with 30mL of deionized water, and place them in an ultrasonic oscillator for ultrasonic dissolution. After the precursor salt is fully dissolved, add 10g of γ-Al2O3 carrier with an average particle size of 50nm. After ultrasonication for 30min, transfer to an oil bath for stirring and heating. The heating temperature is set to 90℃. After the solution becomes a molten state, set the heating temperature to 150℃ until the water in the beaker is completely evaporated. Collect the solid material and grind it thoroughly. The ground powder is placed in a crucible and heated to 800℃ in a muffle furnace at a heating rate of 5℃ / min. Keep warm for 4h and anneal to obtain 20%Fe-20%Ni / γ-Al2O3 catalyst powder.
[0052] (2) Preparation of coating catalyst slurry Weigh 10 g of the catalyst powder obtained in step (1) into a ball mill, then add 1.5 g of polymethyl methacrylate, 2 g of aluminum sol, 0.2 g of carboxymethyl cellulose, 0.2 g of polyoxypropylene glycerol ether, 1 g of glycerol in sequence, and finally add zirconium balls with average diameters of 5 mm and 8 mm, with a total mass of 25 g of zirconium balls; ball mill for 15 min in a planetary ball mill at a speed of 800 r / min, filter out the zirconium balls after ball milling, and obtain a 20% Fe-20% Ni / γ-Al2O3 catalyst slurry.
[0053] (3) Catalyst slurry coating After chamfering the air inlet head of the sensor chip, use polyvinyl butyral to seal the air inlet head, use an immersion and pulling machine to completely immerse the chip head in the catalyst slurry, immerse for 30 seconds, pull it upward at a speed of 100μm / s, and dry it in a 50℃ oven after coating. Repeat the immersion and drying, then place it in a muffle furnace and bake it at 900℃ for 2h. After annealing, a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and its coating thickness is measured to be 418μm.
[0054] Example 6 An embodiment of the present invention provides a method for preparing a nitrogen oxygen sensor, comprising the following steps: (1) Catalyst powder preparation Weigh 16.907g of ferric chloride hexahydrate and 5.3049g of nickel chloride hexahydrate, add them to a beaker filled with 30mL of deionized water, and place them in an ultrasonic oscillator for ultrasonic dissolution. After the precursor salt is fully dissolved, add 10g of γ-Al2O3 carrier with an average particle size of 50nm. After ultrasonication for 30min, transfer to an oil bath for stirring and heating. The heating temperature is set to 90℃. After the solution becomes a molten state, set the heating temperature to 150℃ until the water in the beaker is completely evaporated. Collect the solid material and grind it thoroughly. The ground powder is placed in a crucible and heated to 800℃ in a muffle furnace at a heating rate of 5℃ / min. Keep warm for 4h and anneal to obtain 30%Fe-10%Ni / γ-Al2O3 catalyst powder.
[0055] (2) Preparation of coating catalyst slurry Weigh 10 g of the catalyst powder obtained in step (1) into a ball mill, and then add 0.5 g of polymethyl methacrylate, 2 g of silica sol, 0.2 g of carboxymethyl cellulose, 0.2 g of polyoxypropylene glycerol ether, and 1 g of glycerol in sequence, and finally add zirconium balls with average diameters of 5 mm and 8 mm, with a total mass of 25 g of zirconium balls; ball mill for 15 min in a planetary ball mill at a speed of 800 r / min, filter out the zirconium balls after ball milling, and obtain a 30% Fe-10% Ni / γ-Al2O3 catalyst slurry.
[0056] (3) Catalyst slurry coating After chamfering the air inlet head of the sensor chip, use polyvinyl butyral to seal the air inlet head, use an immersion and pulling machine to completely immerse the chip head in the catalyst slurry, immerse for 30 seconds, pull it upward at a speed of 100μm / s, and dry it in a 50℃ oven after coating. Repeat the immersion and drying, then place it in a muffle furnace and bake it at 900℃ for 2h. After annealing, a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and its coating thickness is measured to be 482μm.
[0057] Comparative Example 1 The specific preparation steps of this comparative example are roughly the same as those of Example 1, except that: In step (1), only 15.72 g of copper nitrate hexahydrate is added as the precursor salt, and the calcination temperature is 550° C. After calcination and annealing, a 40% Cu / γ-Al2O3 catalyst powder is obtained; After annealing in step (3), a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and the coating thickness is measured to be 445 μm.
[0058] Comparative Example 2 The specific preparation steps of this comparative example are roughly the same as those of Example 1, except that: The powder catalyst in step (1) is replaced by a physical mixture of commercial nano-iron oxide, nano-nickel oxide and nano-aluminum oxide; After annealing in step (3), a nitrogen oxygen sensor chip coated with a porous catalyst is obtained, and the coating thickness is measured to be 469 μm.
[0059] Comparative Example 3 The specific preparation steps of this comparative example are roughly the same as those of Example 1, except that: The intake end of the NOx sensor chip is not coated with a porous catalyst.
[0060] Comparative Example 4 The specific preparation steps of this comparative example are roughly the same as those of Example 1, except that: The coating thickness of the comparative example was 165 μm.
[0061] Comparative Example 5 The specific preparation steps of this comparative example are roughly the same as those of Example 1, except that: The coating thickness of the comparative example was 712 μm.
[0062] Test Case The electrical performance tests were performed on the nitrogen oxygen sensor chips prepared in Examples 1 to 6 and Comparative Examples 1 to 5.
[0063] Specifically, the pin end of the sensor chip is inserted into the chip test channel, the resistance of the heating electrode is detected and calibrated, a metal protective cover is used to provide a closed space for the chip, N2 containing 8% O2 is introduced, and the total flow rate is controlled to be 0.2SLM using a mass flowmeter. A voltage is applied to the heating electrode to make the temperature of the sensor head reach 860°C, and a pump voltage is applied to each chamber of the sensor in turn to detect the single pump limiting current. Then, each pump is controlled in conjunction to detect whether the sensor chip can achieve closed-loop control to ensure that the sensor chip head can operate normally after coating the catalyst. After the nitrogen oxide sensor is stable under the above conditions, the total flow rate is fixed at 0.2 SLM, and a certain concentration of NH3 and / or NO is introduced. The limiting current IP2 of the third chamber after stabilization is noted and recorded. The size of its IP2 value reflects the ability of the coated porous catalyst to catalyze the oxidation of NH3 to N2. The smaller the IP2 value, the higher the N2 selectivity of the porous catalyst, and the larger the IP2 value, the lower the N2 selectivity of the porous catalyst.
[0064] Table 1 shows the evaluation results and relative errors of the limiting current value IP2 of the nitrogen oxide sensor after different porous catalysts were coated on Examples 1 to 6 and Comparative Examples 1 to 5.
[0065] Table 1 Serial number Experiment number Coating thickness <![CDATA[NH3 concentration]]> NO concentration IP2 size δ Relative error 1 Example 1 516μm 50ppm 50ppm 139nA 4.51% 2 Example 2 448μm 50ppm 50ppm 143nA 7.52% 3 Example 3 428μm 50ppm 50ppm 147nA 10.52% 4 Example 4 459μm 50ppm 50ppm 160nA 20.30% 5 Example 5 418μm 50ppm 50ppm 142nA 6.77% 6 Example 6 482μm 50ppm 50ppm 152nA 14.29% 7 Comparative Example 1 445μm 50ppm 50ppm 155nA 16.54% 8 Comparative Example 2 469μm 50ppm 50ppm 170nA 27.82% 9 Comparative Example 3 — 50ppm 50ppm 235nA — 10 Comparative Example 3 — 50ppm — 98nA — 11 Comparative Example 3 — — 50ppm 133nA — 12 Example 1 516μm 50ppm — 11nA — 13 Example 1 516μm — 50ppm 131nA — 14 Comparative Example 4 165μm 50ppm 50ppm 206nA 54.89% 15 Comparative Example 5 712μm 50ppm 50ppm 140nA 5.26% It should be noted that the test conditions of each experiment in Table 1 are: temperature 860° C., flow rate 0.2 SLM, O28%, 50 ppm NH3 and / or 50 ppm NH3 and N2 balance.
[0066] The calculation formula of relative error in Table 1 is:
[0067] Take the calculation result in sequence number 1 as an example to illustrate: The limiting current value IP2 = 133nA tested by the NOx sensor without porous catalyst in No. 11 is the true value, reflecting the true concentration of NO in the atmosphere; the difference between the limiting current in No. 1 and the limiting current in No. 11 is the absolute error, so
[0068] Serial numbers 1, 12, and 13 are electrical performance tests of Example 1 under different atmospheres. The comparison results show that the porous catalyst coating has a higher N2 selectivity for NH3 oxidation and has almost no effect on NO detection under this condition.
[0069] No. 1, 14, and 15 are electrical performance tests of the same catalyst formula but different coating thicknesses. The results show that the thinner coating thickness cannot meet the requirements and the relative error is large; while the thicker coating thickness does not further improve the N2 selectivity. In addition, as the coating thickness increases, the gas diffusion resistance will increase, resulting in a slower response speed.
[0070] The NH3 oxidation porous catalyst coating prepared in the embodiments of the present invention has high N2 selectivity, especially the 30%Fe-10%Ni / γ-Al2O3 catalyst prepared in Example 1, which has the best catalytic performance. Under this condition, the limiting current IP2 after coating on the head of the nitrogen oxide sensor is lower than that of others, and its relative error is only 4.51%.
[0071] Secondly, the electrical performance of the nitrogen oxygen sensor coated with 30% Fe-10% Ni / γ-Al2O3 porous catalyst in Example 1 was tested only at different NH3 concentrations. Figure 6 As shown; it can be seen from the figure that at the NH3 concentration of 0~150ppm, there is a lower limiting current IP2, indicating that it has a higher N2 selectivity.
[0072] In addition, a long-term stability test was conducted on the nitrogen oxygen sensor coated with 30% Fe-10% Ni / γ-Al2O3 porous catalyst in Example 1. Figure 7 As shown, the results show that the nitrogen oxygen sensor coated with 30%Fe-10%Ni / γ-Al2O3 porous catalyst in Example 1 has good stability.
[0073] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An ammonia oxidation catalyst, characterized in that The composition comprises the following components by mass fraction: 100 parts of catalyst powder, 1-20 parts of pore former, 10-20 parts of binder, 0.5-5 parts of thickener, 0.5-5 parts of defoamer and 10-20 parts of solvent; The catalyst powder includes a catalyst carrier and a catalytically active component supported on the catalyst carrier; The precursor salt used for the catalytically active component is one or more of ferric nitrate, nickel nitrate, ferric chloride, nickel chloride, and copper nitrate; The catalyst carrier is one or more of SiC, SiO2, γ-Al2O3, and ZrO2.
2. An ammonia oxidation catalyst according to claim 1, characterized in that: The pore-forming agent is one or more of carbon powder, polymethyl methacrylate, starch, and polyvinyl pyrrolidone.
3. An ammonia oxidation catalyst according to claim 1, characterized in that: The binder is one or more of alumina sol, silica sol and diaspore; the thickener is one or more of gelatin, carboxymethyl cellulose, dextrin and gum arabic.
4. An ammonia oxidation catalyst according to claim 1, characterized in that: The defoaming agent is one or more of polydimethylsiloxane, polyoxypropylene glyceryl ether, and stearic acid glycol ester; the solvent is one or a mixture of deionized water, ethanol, glycerol, and acetic acid.
5. The method for preparing the ammonia oxidation catalyst according to any one of claims 1 to 4, characterized in that: The steps include: 1) Add the precursor salt of the catalytically active component into water and dissolve it; 2) Add the catalyst carrier and heat until the water evaporates; 3) Collect the solid matter, grind it, and then calcine it to obtain catalyst powder; 4) The catalyst powder is mixed with a pore former, a binder, a thickener, a defoamer and a solvent, and mixed in a ball mill to obtain an ammonia oxidation catalyst slurry.
6. The method for preparing an ammonia oxidation catalyst according to claim 5, characterized in that: In step 2), an oil bath is used for stirring and heating at a temperature of 50-200°C; In the step 3), the calcination temperature is 500-900° C. and the temperature is kept for 2-6 hours.
7. A nitrogen oxygen sensor chip, characterized in that: The air inlet of the nitrogen oxygen sensor chip is coated on the outside with the ammonia oxidation catalyst according to any one of claims 1 to 4 or the ammonia oxidation catalyst prepared by the preparation method according to claim 5 or 6.
8. The nitrogen oxygen sensor chip according to claim 7, characterized in that: The coating thickness of the ammonia oxidation catalyst is 100~800μm.
9. The method for preparing a nitrogen oxygen sensor chip according to claim 7 or 8, characterized in that: The steps include: 1) Use a sealing agent to seal the air inlet head of the sensor chip; 2) vertically placing the sensor chip into the catalyst slurry according to claim 5, so that the head of the sensor chip is immersed in the catalyst slurry and is completely covered by the slurry; 3) After dipping for a certain period of time, the sensor chip is pulled upward to complete one dipping, dried, and then the dipping and drying processes are repeated. Finally, the sensor chip is baked to obtain the nitrogen oxygen sensor chip.
10. The method for preparing a nitrogen oxygen sensor chip according to claim 9, characterized in that: In step 3), the immersion time is 10~80s, the pulling speed is 50~1000μm / s, the number of repeated immersion and pulling is 1~N, and the drying temperature is 45~150℃; the calcination temperature of the sensor chip after coating is 800~1200℃, and the insulation time is 0.5~4h.
Citation Information
Patent Citations
Metal loaded catalyst used for selective catalytic oxidation of ammonia, preparation method and application thereof
CN101979140A
Catalyst for selective oxidation of nh3 to n2 and method for preparing the same
CN102740966A
Multifunctional protective cover for NOx sensor and preparation method of coating of protective cover
CN104792846A
Waste gas treatment system
CN204357536U
Ammonia oxidation catalyst
EP0562567A1